Nanocrystalline Mn-Zn-ferrite by novel oxalato-hydrazinated complex method - Kanade, K. G.; Amalnerkar, Dinesh P.; Potdar, H. S.; Kale, B. B. (Materials Chemistry and Physics, 2009)
We report here for the first time the synthesis of technologically important ferrite, using a metal oxalato-hydrazinate (MOH) complex method. The MOH complex of iron-manganese-zinc was synthesized at room temperature using the precursors, ferrous ammonium sulphate, manganese acetate and zinc acetate. Thermo-gravimetric studies of MOH intermediate showed complete phase formation of MnZnFe(2)O(4) at 280 degrees C. XRD data showed the formation of single phase cubic spinel MnZnFe(2)O(4). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) demonstrate the spherical shape particle morphology. TEM images indicated the particle size of ferrite powder in the range of 20-36 nm. Magnetization of synthesized nano-sized Mn(0.69)Zn(.0.19)Fe(2.12)O(4) was observed coercive force (H(c)) at 127.82 Oe with a saturation magnetization (M(s)), 34.5 emu g(-1) using vibrating sample magnetometer (VSM) at room temperature. Mossbauer study of nano-sized ferrite powder showed super-paramagnteic behavior. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: crystal structure; Magnetic materials; Mn-Zn-ferrite; Nanostructures; Optical properties